Final-year hospitality students’ perceptions of labour shortages in Malaysia's hospitality sector - Muniar, Fawwaz Nu’man; Hamidi, Nur Balqis Zulaikha; Samsudin, Azlina; Wan Kamarudin, Wan Nor Bayah; Mahusain, Muhammad Afnan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The hospitality industry plays a vital role in Malaysia’s economy, contributing significantly to GDP, employment, and cultural promotion. However, the sector faces persistent labour shortages, worsened by high turnover, negative job perceptions, and the lingering effects of the COVID-19 pandemic. Despite increasing numbers of hospitality graduates, many remain reluctant to pursue careers in the industry for which they are trained. This study, therefore, examines the perceptions of final-year hospitality students regarding the key factors contributing to labour shortages in Malaysia’s hospitality sector. A quantitative survey was conducted with 101 UiTM Dungun students from Hotel Management, Food Service Management, and Culinary Arts programmes, focusing on four dimensions: nature of work, social status, working hours, and job insecurity. Descriptive and correlation analyses revealed that working hours were the most influential factor (M = 4.15), strongly associated with social status (r = 0.709). Findings suggest that long and inflexible schedules reduce career attractiveness, while concerns about low occupational prestige (M = 3.85) and job insecurity (M = 3.62) also discourage long-term commitment. The nature of work was perceived more positively (M = 3.81), yet its physical and emotional demands still acted as deterrents. These results indicate that labour shortages are driven less by a lack of graduate interest than by unfavourable perceptions of work conditions, industry image, and stability. Future implications highlight the need for stronger industry-academia collaboration. Employers are encouraged to introduce flexible scheduling, structured career pathways, and employee retention initiatives; meanwhile, educational institutions should bridge expectation gaps through practical exposure and industry engagement. Addressing these systemic challenges holistically is essential to sustaining Malaysia’s hospitality workforce and ensuring the sector’s long-term competitiveness.